Gender and thrombolysis therapy in stroke patients with incidence of dyslipidemia - Brice Blum; Leah Wormack; Mason Holtel; Alexandria Penwell; Shyyon Lari; Brittany Walker; Thomas I. Nathaniel (BMC, 2019)
Abstract Background When untreated, dyslipidemia is a higher risk factor for stroke and stroke-related mortality in men than in women. However, when dyslipidemia is treated the risk reduction is the same, but men benefited from mortality reduction more than women. Whether there is a gender difference in exclusion criteria for the use of recombinant tissue plasminogen activator (rtPA) or thrombolysis therapy in an acute ischemic stroke subpopulation with dyslipidemia is yet to be investigated. Method In a dyslipidemic stroke population obtained from a stroke registry, gender differences in exclusion risk factors were determined using clinical and demographic variables. Univariate analysis compared the recombinant tissue plasminogen activator (rtPA) group and the no rtPA group. Multiple regression analysis was used to determine demographic and clinical factors associated with inclusion and exclusion for rtPA in the total dyslipidemic stroke population and the subsets of the male and female population. The regression model was tested using the Hosmer-Lemeshow test, for the overall correct classification percentage. Significant interactions and multicollinearity between independent variables were examined using variance inflation factors. Results A total of 769 patients presented with acute ischemic stroke with incidence dyslipidemia; 325 received rtPA while 444 were excluded from rtPA. Of those excluded from rtPA, 54.30% were female and 45.72% were male. In an adjusted analysis, female patients with increased age (OR = 1.024, 95% CI, 1.001-1.047, P < 0.05), with a history of carotid artery stenosis (OR = 7.063, 95% CI, 1.506-33.134, P < 0.05), and previous stroke (OR = 1.978, 95% CI, 1.136-3.442, P < 0.05) were more likely to be excluded from rtPA. Male patients with atrial fibrillation (OR = 2.053, 95% CI, 1.059-3.978, P = 0.033), carotid artery stenosis (OR = 2.400, 95% CI, 1.062-5.424, P = 0.035), and previous stroke (OR = 1.785, 95% CI, 1.063-2.998, P = 0.028) were more likely to be excluded from rtPA. Conclusion Although there are some similarities in the clinical risk factors for exclusion in both male and female stroke patients with incidence of dyslipidemia, there are differences as well. Elderly female stroke patients with incidence of dyslipidemia are more likely to be excluded from rtPA, even after adjustment for the effect of confounding variables. Further research should focus on how identified clinical risk factors can be targeted and managed to improve the use of rtPA in elderly female acute ischemic stroke population with incidence of dyslipidemia.